Association between magnesium intake and the risk of anemia among adults in the United States - Huang, Jungao; Xu, Jing; Ye, Ping; Xin, Xiaoqin (Frontiers in Nutrition, 2023)
Background Magnesium deficiency is related to an increased risk of anemia, but epidemiological evidence supporting this association remains scarce. The purpose of the present survey was to evaluate the relationship between dietary magnesium intake and the risk of anemia. Methods In total, 13,423 participants aged 20–80 years were enrolled using data from the National Health and Nutrition Examination Survey 2011–2016. Magnesium consumption was evaluated using 24 h dietary recalls. Multivariable generalized linear models were developed to demonstrate the association between dietary magnesium intake and the prevalence of anemia. Results An inverse association between dietary magnesium intake and the risk of anemia was detected based on a full adjustment model. We evaluated magnesium intake as a categorical variable (five quartiles). Compared with the lowest value, the highest multivariate adjusted odds ratio (95% confidence interval) for anemia was 0.64 (0.46–0.89). Stratified analyses revealed a reverse relationship between magnesium intake and anemia in women. However, no significant association was observed in men (pfor trend = 0.376). A similar reverse association was found among the older group (aged ≥60 years). Conclusion Magnesium deficiency is closely related to a higher rate of anemia occurrence, especially among women and older Americans. Further larger-scale prospective studies are required to confirm these conclusions.